Catalyzing collaborative monitoring processes in joint forest management situations: the Mafungautsi forest case, Zimbabwe - Mutimukuru, T.; Kozanayi, W.; Nyirenda, R. (2006)
Recent forest management initiatives in developing countries emphasize active participation of local people. However, many such attempts have been unsuccessful because little attention was directed at promoting conscious and joint learning processes. One way to enhance joint learning is through collaborative monitoring (CM) and reflection processes. This article explores the contribution that collaborative monitoring processes make toward improving forest management within a context characterized by multiple stakeholders with often-conflicting interests. The Mafungautsi case has shown that initiating CM processes requires careful facilitation of negotiations related to the goals, approach, sharing of information; and development of platforms on which learning will take place. We conclude, based on evidence from Mafungautsi, that CM processes can contribute to improving forest management in multistakeholder landscapes if sufficient attention is paid in creating appropriate reflection and learning platforms.